Taxonomic notes on some photosynthetic species of Neottia (Orchidaceae) from North Temperate Asia - Efimov, Petr G. (Phytotaxa, 2019)
Taxonomy of two species of genus Neottia, N. puberula and N. pinetorum, is discussed. A widely used name Listera savatieri is lectotypified, and by lectotypification, it falls into the synonymy of Neottia pinetorum. A poorly known species from Central Asia, N. tianschanica, is shown to be synonymous to N. pinetorum.